The Politics of Public Space: Toronto’s Yonge Street Pedestrian Mall, 1971–1974 - Ross, Daniel (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2018)
Beginning in the 1950s, hundreds of cities in Canada and the United States experimented with closing major downtown shopping streets to automobile traffic and opening them up to pedestrians. The few scholars who have studied these pedestrian malls have emphasized their failure as an economic revitalization initiative: hopes that creating new public spaces would lure suburban shoppers downtown were frustrated, and few are still in operation today. This article takes a different approach, using a rich archive of sources on Toronto’s Yonge Street pedestrian mall (1971–4) to analyze its life as a public space. This is a revealing angle from which to understand the North American downtown in a period of automobility, urban renewal, and municipal reform. Over four summers, a range of historical actors invested the mall concept with their hopes and fears for the urban future and appropriated its spaces through everyday practices. As a result, the Yonge Street pedestrian mall acquired multiple identities: a site of sociability and displays of civic pride; a protest against pollution; a marketplace; a gathering place for youth; a spectacle of downtown life. This article explores the representations and street life that created these images of the mall, arguing that the experiment is best understood as a contested and disorderly public space. It also places the different historical actors and ideas that met on Yonge Street in the larger context of the postwar North American city.